Surto de parvovirose cardíaca em filhotes de cães no Brasil - Souto, Erick Platiní Ferreira de (2018)
We describe the epidemiological, clinical, pathological and immunohistochemical aspects of parvoviral myocarditis outbreak in puppies. The outbreak occurred in a kennel located in Parnamirim, Rio Grande do Norte, Northeastern of Brazil. In a litter of nine pups, one was stillbirth and six died between 35-57 days of age after cardiopulmonary clinical signs with evolution of 10 minutes to three days. Of the six puppies that died, two were sent for necropsy. On gross examination, both animals had discreet pericardial effusion, markedly distended heart, diffuse pallor in epicardial and myocardial surfaces and dilation of the left ventricular cavity. The lungs were observed multifocal reddish areas in the pleural surface and at cutting flowed foamed and slightly red liquid. The liver was diffusely increased in size, with lobular standard accentuation and pale areas interspersed with dark areas wich deepened in the parenchyma. Microscopically observed linfohistiocítica myocarditis, necrotizing, associated with interstitial fibrosis and basophilic intranuclear viral inclusions corpuscles in cardiomyocytes. In the lungs there were edema and interstitial pneumonia and in the liver was noted centrilobular to mediozonal degeneration and necrosis associated with congestion and hemorrhage. The diagnosis was confirmed by immunohistochemistry. The parvoviral myocarditis can occasionally occur in puppies of bitches that have not been effectively vaccinated. This clinical form of the disease characterized by cardiorespiratory changes and hyperacute or acute death of the affected animals.